Dyah Kunthi Talibrata Sebagai Representasi Profil Wanita Jawa Sejati - Hartini (Madaniyah, 2014)
The Javanese community in the wayang story has a woman who is worth emulating, namely Dyah Ayu Kunthi. Dyah Ayu Kunthi Talibrata's life journey is very sad, but she is able to show self-esteem and make all women finally admire her qualities. Dyah Ayu Kunthi, is the son of a king who has good feminine qualities and can be made a role model for women so that negative titles such as women are only as kanca wingking (friends behind), kanca turu (sleeping companions) who are at all considered to be no role in the family can be eliminated.